IPF – Die erste Dekade: 10 Years of Artistic Research in the Performing Arts and Film - Rey, Anton; Schmidt, Yvonne -1982; Whigham, Jennifer (Zurich Zurich University of Arts, 2018)
10 years IPF – The Institute for the Performing Arts and Film at Zurich University of the Arts with its research focus “Performative Practice” and “Film” plays a leading role in the context of the debate on research at arts universities. For a decade, the IPF has been producing, initiating and supervising research studies, events and publication formats, which establish a dialogue between scientific and artistic processes. The topics are divided into the fields of research on art, research for art and research with art. The workbook contains an account of the previous activities.
for more information see: https://www.theaterderzeit.de/buch/ipf_%E2%80%93_die_erste_dekade
Keywords: Theater history; Artistic research